Um método de busca usando algoritmo genético para programação reativa da produção de sistemas de manufatura com recursos compartilhados - Deriz, Ana Claudia (2007)
Search strategies have been used to solve the problem of scheduling of Manufacturing Systems with Shared Resources. However, depending on the size and complexity of the manufacturing system, the response time of the search becomes critical. Reseaches aim to use of Genetic Algorithms as a search method to solve the scheduling problem. This work proposes a modeling of Genetic Algorithm to solve this problem having as performance criteria the minimum makespan of the scheduling and obtaining a low response time of the search.